"Improving of Motivation and Learning Achievement of Mathematics by Using Computer-Based Learning Media on Quadratic Function Topic in Grade X SMAN 1 Minas" - Akhidah, Siti Misi (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Motivation and learning achievement of studentsare a problem that is closely related to the success of students. Motivationand student learning achievement are still low, thesecould be seen from the end of semester test. One of the efforts taken by teacher in learning process is to use Macromedia flash programmingas computer-based learning media on the topic of quadratic function in class X to improve motivation and learning achievement ofstudents. The goal is to guide students to get the concept of understanding quadratic function topic.This is a class action research on learning mathematics. The subject of this research is students of grade X of SMAN 1 Minas. The research consists of two cycles. Each cycle consists of four stages: planning, implementation, observation, and reflection. The instruments used to observe the treatment and results of the action are the students motivation observation sheets and studentâs test results sheet.Based on the results of the study, motivation and learning achievement can be improved by using computer-based learning media quadratic function in learning mathematics in class X SMAN 1 Minas. This can be seen from the increase of learning motivation which increase from cycle 1 to cycle II by 22,78% and result of learning increase from cycle I to cycle II equal to 39%.Improvelearning achievementis easy to achieve because in the use of this media students closer to the application. The use of quadratic programming media programs is designed to convey the concept of learning topics with students directly using this program to learn.The program which is made by usingsMacromedia Flash is more interactive with the form of animation motion and sound more complex and can be included simple programs that can not be done by using Microsoft Powerpoint. After that the students are expected to find their own concepts that must be understood in the matter of quadratic functions and solve all problems related to quadratic functions more easily. Finally, it can be concluded that using computer-based learning media can help students to build the concept of understanding quadratic function topic